(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Medical education has been focused on making doctors competent in effectively delivering the health care system. The health profession is a complex entity dealing with multiple domains and dimensions of human life. All three important domains namely cognitive, psychomotor, and affective domains are equally important. With the advent of the competency-based medical education (CBME) system proposed by the National Medical Commission (NMC) in India, the procedure of making successful and competent Indian Medical Graduates (IMG) has been started a few years back. This article is about the scope and ethical aspects of implementing the CBME curriculum in India, which is reviewed and discussed here. As per the requirement, the curriculum has radically changed in recent years. However, during the COVID-19 pandemic, it has been greatly affected by the implementation of a nationwide online virtual teaching mode. The theory and practical aspects of medical teaching underwent a different dealing during that period and obviously, the question arose whether the affective domain teaching is effective and impactful in that virtual online mode. The affective domain consists of Attitude, Ethics, and Communication (AETCOM) which are essential for treating and interacting with patients which is to be taught in the undergraduate study period of medical course. This article delves deep into the possibilities with the pros and cons of such a situation from an insightful perspective.